Improving the availability of vaccines in primary healthcare facilities in South Africa: is the time right for a system redesign process?. Issue 1 (31st January 2022) - Iwu-Jaja, Chinwe Juliana; Jordan, Portia; Ngcobo, Ntombenhle; Jaca, Anelisa; Iwu, Chidozie Declan; Mulenga, Modest; Wiysonge, Charles
ABSTRACT: An uninterrupted supply of vaccines at different supply chain levels is a basic component of a functional immunization programme and care service. There can be no progress toward achieving universal health coverage and sustainable development without continuous availability of essential medicines and vaccines in healthcare facilities. Shortages of vaccines, particularly at health facility level is an issue of grave concern that requires urgent attention in South Africa. The causes of vaccine stock-outs are multifactorial and may be linked to a broader systems issue. These factors include challenges at higher levels such as delays in the delivery of stock from the pharmaceutical depot; health facility level factors, which include a lack of commitment from healthcare workers and managers; human resource factors, such as, staff shortages, and lack of skilled personnel. Therefore, there is a compelling need to address the factors associated with shortages of vaccines in health facilities. This paper highlights the challenges of vaccine availability in South Africa, the associated factors, the available interventions, and recommended interventions for the expanded programme on immunization in South Africa. We propose a system redesign approach as a potentially useful intervention.